Regulation of Phosphatidic Acid Metabolism by Sphingolipids in the Central Nervous System - Pasquare, Susana J. (2011)
This paper explores the way ceramide, sphingosine, ceramide 1-phosphate, and sphingosine 1-phosphate modulate the generation of second lipid messengers from phosphatidic acid in two experimental models of the central nervous system: in vertebrate rod outer segments prepared from dark-adapted retinas as well as in rod outer segments prepared from light-adapted retinas and in rat cerebral cortex synaptosomes under physiological aging conditions. Particular attention is paid to lipid phosphate phosphatase, diacylglycerol lipase, and monoacylglycerol lipase. Based on the findings reported in this paper, it can be concluded that proteins related to phototransduction phenomena are involved in the effects derived from sphingosine 1-phosphate/sphingosine or ceramide 1-phosphate/ceramide and that age-related changes occur in the metabolism of phosphatidic acid from cerebral cortex synaptosomes in the presence of either sphingosine 1-phosphate/sphingosine or ceramide 1-phosphate/ceramide. The present paper demonstrates, in two different models of central nervous system, how sphingolipids influence phosphatidic acid metabolism under different physiological conditions such as light and aging.